2018
DOI: 10.1891/2474-8684.2.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Women of Color and Work–Life Balance in an Urban Environment: What Is Reality?

Abstract: Background:Work–life balance is a significant issue for women of color in an urban environment whether one is engaged in academia, traditional work, remote/dispersed work, or entrepreneurial work. As women of color attempt to address the tangible and intangible aspects of the “life” portion associated with the work–life balance discussion, elements such as race, ethnicity, religion, spirituality, and caregiver demands toward primary and extended family are often ignored.Objective:This article expands the work–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…concurs that development is needed in postgraduate supervision Kachchaf et al (2015). as well asAlleman et al (2018) also found that work-life balance was a challenge for Black women in academia. It is important to note that the Black women academics are not just focusing on academic matters obligations, but they do have domestic activities that they still need to carry out when they are at home.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…concurs that development is needed in postgraduate supervision Kachchaf et al (2015). as well asAlleman et al (2018) also found that work-life balance was a challenge for Black women in academia. It is important to note that the Black women academics are not just focusing on academic matters obligations, but they do have domestic activities that they still need to carry out when they are at home.…”
mentioning
confidence: 67%
“…Sonn (2016) concurs that development is needed in postgraduate supervision. Kachchaf et al (2015) as well as Alleman et al (2018) are of the opinion that work-life balance is a significant issue for women of colour in academia. Msimanga (2016, abstract) states: "the complex relationship of time, career and context, I argue that the time of womanhood, blackness and motherhood in academia is out of joint".…”
Section: Constraints In Advancing Black Women Academicsmentioning
confidence: 99%
“…1 There are multiple definitions and usages of the term emotional labor, many not covered here. It is important to note that the way in which black feminists, such as Kimberley Seals Allers (2018) and Leah Cowan (2016), have been using the term emotional labor to talk about the work they do to counter everyday racism has a strong, and vital structural critique of power, though this will not be explored in this article.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%